Why my recurrence is getting wrong?

I was solving this question on hackerearth -

I came through the recurrence relation
(doesn’t works correctly

if(dp[N][K] != -1)
	return dp[N][K];
if(K == 0)
	return 0;
if(K > N)
	return 0;
if(N == K)
	return 1;
else
{
	dp[N-K][K] = solve(N-K,K);   // Kth number is selected,problem reduced to subproblem with new sum as N - K
	dp[N][K - 1] = solve(N,K - 1);  // Kth number isn't selected,we need to explore upto (K - 1) now
	dp[N][K] = dp[N-K][K] + dp[N][K - 1];
	return dp[N][K];
}

instead of(works fine)

if(dp[N][K] != -1)
	return dp[N][K];
if(K == 0)
	return 0;
if(K > N)
	return 0;
if(N == K)
	return 1;
else
{
	dp[N-K][K] = solve(N-K,K);
	dp[N][K + 1] = solve(N,K + 1);
	dp[N][K] = dp[N-K][K] + dp[N][K + 1];
	return dp[N][K];
}

Whats the difference between 2 approaches for solving the above problem?